Tetrathiobacter kashmirensis gen. nov., sp. nov., a novel mesophilic, neutrophilic, tetrathionate-oxidizing, facultatively chemolithotrophic betaproteobacterium isolated from soil from a temperate orchard in Jammu and Kashmir, India - Ghosh, Wriddhiman; Bagchi, Angshuman; Mandal, Sukhendu; Dam, Bomba; Roy, Pradosh (International journal of systematic and evolutionary microbiology, 2005)
1 Department of Microbiology, Bose Institute, P-1/12 C. I. T. Scheme, VII M, Kolkata 700 054, India 2 Bioinformatics Center, Bose Institute, P-1/12 C. I. T. Scheme, VII M, Kolkata 700 054, India Correspondence Wriddhiman Ghosh Wrimanatrediffmail.com Twelve chemolithotrophic strains were isolated from temperate orchard soil on reduced sulfur compounds as energy and electron sources and characterized on the basis of their physiological properties and ability to oxidize various reduced sulfur compounds. The new isolates could oxidize tetrathionate as well as thiosulfate, and oxidation of the latter involved conversion of thiosulfate to tetrathionate followed by its accumulation and eventual oxidation to sulfate, manifested in the production of acid. The mesophilic, neutrophilic, Gram-negative and coccoid bacteria had a respiratory metabolism. Physiologically and biochemically, all the strains were more or less similar, differing only in their growth rates and ability to utilize a few carbon compounds as single heterotrophic substrates. 16S rRNA gene sequence analysis was performed with five representative strains, which revealed a high degree of similarity ( 99 %) among them and placed the cluster in the Betaproteobacteria . The strains showed low levels (93·595·3 %) of 16S rRNA gene sequence similarity to Pigmentiphaga kullae , Achromobacter xylosoxidans , Pelistega europaea and species belonging to the genera Alcaligenes , Taylorella and Bordetella . The taxonomic coherence of the new isolates was confirmed by DNADNA hybridization. On the basis of their uniformly low 16S rRNA gene sequence similarities to species of all the closest genera, unique fatty acid profile, distinct G+C content (5455·2 mol%) and phenotypic characteristics that include efficient chemolithotrophic utilization of tetrathionate, the organisms were classified in a new genus, Tetrathiobacter gen. nov. In the absence of any significant discriminatory phenotypic or genotypic characteristics, all the new isolates are considered to constitute a single species, for which the name Tetrathiobacter kashmirensis sp. nov. (type strain WT001 T =LMG 22695 T =MTCC 7002 T ) is proposed. Published online ahead of print on 29 April 2005 as DOI 10.1099/ijs.0.63595-0. The GenBank/EMBL/DDBJ accession numbers for the 16S rRNA gene sequences of strains WT001 T , 445a, 445c, WGT and WPT and are AJ864470 AJ864474, respectively. An example AFLP PCR profile and a UPGMA phenogram are available as supplementary material in IJSEM Online.